PENGARUH VARIABEL BAURAN PEMASARAN TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE OBJEK WISATA WADUK GAJAH MUNGKUR WONOGIRI - Bellinda Nur Annisa, Bambang Mursito & Sudarwati (Universitas Slamet Riyadi, 2018)
This research have the goal to know how big the effect of the marketing mixvariable concerning the tourist decision in Gajah Mungkur Lake Tourism object ofWonogiri, in Simultaneous and partial. Respondent in this research are the visitor ofGajah Mungkur Lake Tourism of Wonogiri with the sample about 100 respondent,taking the data using accidental sampling method. Quantitative method with questioneras the submitted toll. Double linear regression analysis technique with SPSS forwindows. Based on the result of F test analysis knowing that marketing mix variablehave the effect in simultaneous concerning visitor decision. The result of F test analysisknowing that marketing mix variable have the positive effect and significant to the visitordecision. Adjusted R square analysis (R2) as big as 0,507, this is showing that marketingmix variable have the effect concerning visitor decision as big as 50, 7 %, while the restas big as 40,3% not explained in this research.Keywords: Product, Price, Promotion, Location, Person, Process, Physical Evidence,Visiting Decision.